The Analysis of the Role & Obligations of Notaries in Protecting Data Security Based on the Personal Data Protection Law - Frisca, Frisca; Gunadi, Ariawan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Notaries as public officials who are authorized to make authentic deeds carry out their duties and authorities inseparable from the processing of Personal Data, both physical and electronic. Notaries process Personal Data not only for Personal Data subjects, namely Clients, but also for workers or interns, or third parties whose information is provided by the Client. Since the enactment of the PDP Law, Notaries as officials who make authentic deeds in processing Personal Data are not only obliged to maintain the confidentiality of Personal Data, but there are also several other obligations regulated in the PDP Law as an effort to prevent and eradicate potential cybercrime. In this study, the author will dissect the role and obligations of Notaries in the security of Personal Data based on the PDP Law. The study used a normative legal method with a statutory approach and a conceptual approach. Through this study, it is concluded that a Notary as an official who makes authentic deeds has a crucial role, namely as a Personal Data Controller who can determine the purpose and method of processing personal data. Notaries have several obligations as regulated in the PDP Law, including having a basis for processing, ensuring the security of personal data, assessing the impact of Personal Data Protection, recording all personal data processing activities, appointing Personal Data Protection officials, fulfilling the rights of personal data subjects, and others. The ultimate goal of this study is expected to provide knowledge and legal certainty related to Personal Data Protection in notarial practice.